"Oneself as Another": Identification and Mourning in Patrick Modiano's Dora Bruder - Susan Rubin Suleiman (Studies in 20th & 21st Century Literature, 2007)
Taking off from Paul Ricoeur's book Soi-même comme un autre (Oneself as Another), this essay discusses two kinds of identification in Modiano's relation to Dora: identification as appropriation, where the writer "assimilates" Dora's story in order to explore his own relation to his parents, especially his father; and identification as empathy, where the writer underlines the differences between his and Dora's stories and also seeks to come to a historical understanding of what happened to her. In that process, he also evokes the fate of other Jews who, like Dora and her family, were deported from France. I conclude that this kind of empathetic identification leads to mourning, which is the realization that the death of a person has left (as Jacques Lacan puts it) a "hole in the real."
Keywords: Paul Ricoeur; Soi-même comme un autre; identity; Dora Bruder; identification; Jews; holocaust; mourning; death